Chloride-Deficient Diet and Cognitive Deficits - J Gordon Millichap (Pediatric Neurology Briefs)
Distinctive cognitive impairments and a specific neurobehavioral syndrome are reported in 11 of 13 children who had failed to thrive on chloride-deficient formula during infancy.